A Red Blood Cell Membrane-Camouflaged Nanoparticle Counteracts Streptolysin O-Mediated Virulence Phenotypes of Invasive Group A Streptococcus - Escajadillo, Tamara; Olson, Joshua; Luk, Brian T.; Zhang, Liangfang; Nizet, Victor (Frontiers in Pharmacology, 2017)
Group A Streptococcus (GAS), an important human-specific Gram-positive bacterial pathogen, is associated with a broad spectrum of disease, ranging from mild superficial infections such as pharyngitis and impetigo, to serious invasive infections including necrotizing fasciitis and streptococcal toxic shock syndrome. The GAS pore-forming streptolysin O (SLO) is a well characterized virulence factor produced by nearly all GAS clinical isolates. High level expression of SLO is epidemiologically linked to intercontinental dissemination of hypervirulent clonotypes and poor clinical outcomes. SLO can trigger macrophage and neutrophil cell death and/or the inactivation of immune cell functions, and promotes tissue injury and bacterial survival in animal models of infection. In the present work, we describe how the pharmacological presentation of red blood cell (RBC) derived biomimetic nanoparticles (“nanosponges”) can sequester SLO and block the ability of GAS to damage host cells, thereby preserving innate immune function and increasing bacterial clearance in vitro and in vivo. Nanosponge administration protected human neutrophils, macrophages and keratinocytes against SLO-mediated cytoxicity. This therapeutic intervention prevented SLO-induced macrophage apoptosis and increased neutrophil extracellular trap formation, allowing increased GAS killing by the respective phagocytic cell types. In a murine model of GAS necrotizing skin infection, local administration of the biomimetic nanosponges was associated with decreased lesion size and reduced bacterial colony-forming unit recovery. Utilization of a toxin decoy and capture platform that inactivates the secreted SLO before it contacts the host cell membrane, presents a novel virulence factor targeted strategy that could be a powerful adjunctive therapy in severe GAS infections where morbidity and mortality are high despite antibiotic treatment.